2006
DOI: 10.1159/000097952
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Bowel Preparation: Surgical Standard or Past?

Abstract: Background: Preoperative bowel preparation is still routinely used prior to colorectal surgery. This concept is based on traditional and personal empiricism and usually not evidence based. The objective of the present review was to reassess this dogma against the background of the highest level of evidence published thus far. Methods: The Medline database was searched using the search terms ‘preoperative’, ‘bowel’ and ‘preparation’ limited to ‘randomized controlled trials’ and ‘meta-analyses’. Ten randomised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
(90 reference statements)
0
2
0
1
Order By: Relevance
“…Since 1972, Hughes first challenged the incontrovertible routine of MBP; more and more trials have questioned the hollowed tradition. To date, more than 15 randomized clinical trials [4-6, 17, 18, 21-30, 32, 33] and 10 metaanalyses [7][8][9][10][11][12][13][14][15][16] have been published; results from all the researches were in no favor of MBP and make believed that MBP before elective colorectal surgery can safely be abandoned. Some surgical associations and scientific societies have also updated their guidelines [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1972, Hughes first challenged the incontrovertible routine of MBP; more and more trials have questioned the hollowed tradition. To date, more than 15 randomized clinical trials [4-6, 17, 18, 21-30, 32, 33] and 10 metaanalyses [7][8][9][10][11][12][13][14][15][16] have been published; results from all the researches were in no favor of MBP and make believed that MBP before elective colorectal surgery can safely be abandoned. Some surgical associations and scientific societies have also updated their guidelines [1].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several randomized clinical trials have been published to assess the omission of MBP [4][5][6], but the real meaning of MBP is still unclear, especially in laparoscopic colorectal surgery and rectal surgery with low anterior resection. Until now, 10 meta-analyses of randomized clinical trials (RCTs) comparing MBP with no MBP have been published [7][8][9][10][11][12][13][14][15][16]. They concluded that MBP should be omitted since MBP could not reduce infectious postoperative complications and even with higher risk of anastomotic leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Uvedené údaje potvrdzujú skutočnosť, že klinická prax často nie je založená na dôkazoch, ale je založená na tradícii, osobnej empírii. Müller-Stich a spoluautori [24] tvrdia, že predoperačná ortográdna čistota čriev už nie je opodstatnená v kolorektálnej chirurgii vzhľadom na zvýšené riziko únikov v anastomóze. Bucher et al [25] tvrdia, že existujú obmedzené dôkazy na podporu mechanickej prípravy HČ pred plánovaným operačným zákrokom.…”
Section: Diskusiaunclassified